Seasonal changes in endoplasmic reticulum stress and ovarian steroidogenesis in the muskrats (Ondatra zibethicus) - Lu, Wenjing; Gao, Qingjing; Wei, Jinlan; Xie, Wenqian; Zhang, Haolin; Yuan, Zhengrong; Han, Yingying; Weng, Qiang (Frontiers in Endocrinology, 2023)
Many studies have shown roles for endoplasmic reticulum stress (ERS)/unfolded protein response (UPR) signaling cascades with ovarian folliculogenesis, and oocyte maturation. In this study, we investigated seasonal changes in ERS and ovarian steroidogenesis in the muskrats (Ondatra zibethicus) during the breeding season (BS) and non-breeding season (NBS). There were noticeable seasonal variations in the weight and size of muskrat ovaries with values higher in the BS than that in NBS. The circulating luteinizing hormone (LH), follicle-stimulating hormone (FSH), 17β-estradiol, and progesterone of the female muskrats were higher during the BS. The RNA-seq data of ovaries during different seasons revealed 2580 differentially expressed genes, further analysis showed a prominent enrichment of ERS-related pathways and ovarian steroidogenesis pathway. Immunohistochemical results showed that GRP78 and steroidogenic enzymes (P450scc, 3β-HSD, P450c17, and P450arom) existed in the various kinds of cells in muskrat ovaries during the BS and NBS. In ovaries from the BS, the mRNA levels of P450scc, P450arom, P450c17, and 3β-HSD were considerably higher. Furthermore, the expression levels of oxidative stress-related genes (SOD2, CAT, and GPX1) and UPR signal genes (Bip/GRP78, ATF4, ATF6, and XBP1s) were increased strikingly higher during the BS in comparison with the NBS. However, the mRNA levels of CCAAT-enhancer-binding protein homologous protein (CHOP) and caspase-3 had no considerable difference between the BS and NBS. Taken together, these results suggested that UPR signaling associated with the seasonal changes in ovarian steroidogenesis is activated in the BS and the delicate balance in redox regulation is important for seasonal reproduction in the muskrats.